1985
DOI: 10.1016/s0022-5347(17)47660-9
|View full text |Cite
|
Sign up to set email alerts
|

125Iodine Implantation for Carcinoma of the Prostate: 5-Year Survival Free of Disease and Incidence of Local Failure

Abstract: Interstitial implantation with the 125iodine isotope has been used as definitive treatment in 115 patients with localized carcinoma of the prostate. The disease was staged surgically by bilateral pelvic lymphadenectomy in all of the patients. Followup has been for a minimum of 1 year and 64 patients have been followed for a minimum of 5 years. There has been no operative mortality in this series. Mean patient age at implantation was 63 years. Potency has been maintained in 31 of 46 patients (78 per cent) follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…Similar findings were reported by Morton and Peschel [9] and Schellhammer et al [3] who found disease-free survival rates of 84 and 81%, respectively, after 5 years for patients with clinical stage B tumours. The corresponding figures for patients with clinical stage C tumours were 38 and 49%, respectively [3,9]. Likewise, Weyrich et al [10] reported 10-year disease-free survival rates of 60% for stage B2 and of 25% for stage Ci tumours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings were reported by Morton and Peschel [9] and Schellhammer et al [3] who found disease-free survival rates of 84 and 81%, respectively, after 5 years for patients with clinical stage B tumours. The corresponding figures for patients with clinical stage C tumours were 38 and 49%, respectively [3,9]. Likewise, Weyrich et al [10] reported 10-year disease-free survival rates of 60% for stage B2 and of 25% for stage Ci tumours.…”
Section: Discussionsupporting
confidence: 89%
“…The initial results were claimed to be good and the complication rate low [3], Thus, interstitial radiation was suggested as an alternative to radical prostatectomy or external radiation therapy. This paper reports our experience of 125I seed implantation in 37 patients with clinically localized prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…reported as loo%, 81%, 49%, and 41% for patients with stage A2, B, C, and D, disease [20]. Following external beam radiotherapy, 5-year, disease-specific survival has been reported as loo%, loo%, 85%, 83%, and 70% for stage Al, A2, B1, B2 and C disease, respectively [14] At our institution using interstitial 19' Au radiotherapy, 5-year cancer-specific survival was 100% for stage A2 and B1, 90% for B2, and 76% for stage C.…”
mentioning
confidence: 98%
“…Radiotherapy gives useful palliation in the treatment of bony metastases due to prostatic carcinoma (Hope-Stone, 1980) and may relieve ureteric ob- struction (Fossa, 1987). Radical radiotherapy to the prostate has been used extensively in patients with early prostatic carcinoma in an attempt to cure the disease (Bagshawe and Ray, 1983; Dobbs et id., 1985;Schellhammer et al, 1985). However, its use as a palliative measure in order to control distressing symptoms due to advanced local disease has received scant attention in the literature.…”
Section: Discussionmentioning
confidence: 99%